2011
DOI: 10.1021/jp206033x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Phase Behavior of a Quinquethiophene-Based Self-Assembled Monolayer as a Function of Temperature

Abstract: ARTICLEduring layer formation and that a gradual crystalline phase transition occurs upon temperature treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…[3] Typical preparation techniques for the formation of such functional monolayers are solution self-assembly or spin-coating. [4][5][6][7] In particular, for the latter, defined processing parameters need to be identified, otherwise sub-monolayer or multilayer films may form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Typical preparation techniques for the formation of such functional monolayers are solution self-assembly or spin-coating. [4][5][6][7] In particular, for the latter, defined processing parameters need to be identified, otherwise sub-monolayer or multilayer films may form.…”
Section: Introductionmentioning
confidence: 99%
“…Organic thin-film transistors based on semiconducting molecular monolayers are of high scientific interest, as simple solution-based fabrication techniques allow establishing of complex electronic devices, such as code generators [1] or inverters; [2] however, these require high structural quality in terms of layer homogeneity and defined molecular packing. [3] Typical preparation techniques for the formation of such functional monolayers are solution self-assembly or spin-coating. [4][5][6][7] In particular, for the latter, defined processing parameters need to be identified, otherwise sub-monolayer or multilayer films may form.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, frictional studies on low dimensional materials, such as carbon nanotubes (CNT), 1 graphene, [2][3][4][5] and organic monolayers, [6][7][8][9][10][11][12][13] have attracted much interest. Since these low dimensional materials are soft, they are prone to structural deformation during the fabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…Symmetry breaking induced by structural deformation may lead to the deterioration of electrical or electro-mechanical performance for low dimensional materials due to the extremely high surface-tovolume ratios and strong crystallographic dependence of their physical properties. Recent studies revealed that characteristic ripple structures were usually formed in supported [13][14][15][16][17][18] and suspended graphene samples. [19][20][21] We have shown this in a recent study of the friction properties of exfoliated graphene deposited on a SiO 2 substrate, where we discovered the existence of anisotropic friction domains with a 180 • period by measuring the torsion of the AFM cantilever (T LAT ) during lateral scanning of a tip attached to the cantilever.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation